Introducing Circuit Analysis / Fifth Edition - Boylestad Robert L (Merrill Publishing Company, 1987)
Introduction, Currents and Voltages, Resistance, Ohm's Law and Power and Energy, Series Circuits, Para;;e; Circuits, Series-Parallel Networks, Methods of Analysis and Selected Topics, Network Theorems, Capacitors, Magnetic Circuits, Inductors, Sinusoidal Alternating Waveforms, The Basic Elements and Phasors, Series and Parallel ac Circuits, Series-Parallel ac Networks, Methods of Analysis and Selected Topics (ac), Network Theorems (ac), Power (ac), Resonance, Pulse Waveforms and the R-C Response, Polyphase Systems, Nonsinusoidal Circuits, Transformers, Two - Port Parameters (z, y h), Index.